Analysis of survival rates and evaluation of prognostic factors in patients with lung metastases from renal cell carcinoma - D. V. Semyonov; R. V. Orlova; V. I. Shirokorad; S. V. Kostritsky; N. A. Karlova (Сибирский онкологический журнал)
In patients with lung metastases from renal cell cancer (RCC), it is necessary to search for new prognostic factors influencing survival rates. Aim: To analyze survival rates and identify prognostic factors in patients with lung metastases from RCC. Material and methods. We retrospectively analyzed the data from 655 patients with lung metastases from RCC, who were treated at Moscow city oncology Hospital No. 62 (Moscow) and city clinical oncology center (Saint Petersburg) from 2006 to 2022. Of these patients, 241 (36.8 %) were classified into the intermediate prognosis group, and 278 (42.2 %) into the unfavorable prognosis group. The study investigated clinical and morphologic prognostic factors influencing survival rates in patients with lung metastases from RCC. Statistical analysis was performed using Statistica 10.0 software packages (StatSoft, USA) by constructing Kaplan-Meier curves and survival tables, building a mathematical model of survival. Results. The 3- and 5-year OS rates in patients with lung metastases from RCC (N=655) were 48 % [95 % ci 45–53 %] and 27 % [95 % ci 23–31 %], respectively, with a median OS of 34.9 months [95 % ci 30.4–37.4]. in univariate analysis, ECOG status (p<0.001), histological subtype (p<0.001), Fuhrman grade of tumor differentiation (p<0.001), type and number of metastases (p<0.001), metastases to the bones and liver (p<0.001), lymph nodes (p=0.001), prognosis according to IMDC(p<0.001), nephrectomy and metastasectomy (p<0.001) had a negative impact on OS in patients with lung metastases from RCC. In multivariate analysis, ECOG status 3.66 (2.10–6.39, p<0.001), histological subtype 1.49 (1.10–2.01, p=0.009), grade of tumor differentiation according to Fuhrman 1.54 (1.13–2.09, p=0.006), number of metastases 3.63 (1.44–9.16, p=0.006), prognosis according to IMDC2.27 (1.63–3.17, p<0.001), and nephrectomy 1.87 (1.29–2.70, p=0.001) and metastasectomy 0.69 (0.53–0.88, p=0.003) were additional factors influencing OS rates in patients with lung metastases from RCC. Conclusion. In our study, ECOG status, histologic subtype of RCC, Fuhrman grade of tumor differentiation, number of metastases, IMDC prognosis, and nephrectomy and metastasectomy were additional independent prognostic factors affecting OS in patients with lung metastases from RCC. Further studies are needed to investigate prognostic factors in patients with RCC lung metastases to improve the effectiveness of personalized treatment and survival rates.